Nonviolence before King : the politics of being and the Black freedom struggle - Siracusa, Anthony C. (Justice, power, and politics., 2021)
"In the early 1960s, thousands of Black activists used nonviolent direct action to challenge segregation at lunch counters, movie theaters, skating rinks, public pools, and churches across the United States, battling for, and winning, social change. Organizers against segregation had used litigation and protests for decades but not until the advent of nonviolence did they succeed in transforming ingrained patterns of white supremacy on a massive scale. In this book, Anthony C. Siracusa unearths the deeper lineage of anti-war pacifist activists and thinkers from the early twentieth century who developed nonviolence into a revolutionary force for Black liberation"--